Experimental study on air balancing for ACMV system - Tam, Zhi Cong (2018)
Traditional air balancing methods are often time-consuming, costly and inaccurate. The objectives of this project aimed to conduct an experimental study of air balancing on ACMV system based on the comparison of the Manual & Automatic air balancing methods in terms of its accuracy and efficiency. The methods for air balancing was in accordance to industry standards such as the proportionality and step wise method. In order to model real life situations, fixed and varied design flow rate experiments was crafted under both experimental conditions. Maximum Absolute Percentage Error (MAPE) was applied to acquire accuracy whilst efficiency would be total time consumption. Automatic air balancing attained 1.60% and 1.18% more accuracy as compared to manual for both experiment 1 and 2 correspondingly. Automatic air balancing achieved 75% and 80% more efficiency as compared to manual for experiment 1and experiment 2 correspondingly. Due to the limitations of the project, cost and the water loop was not discussed. The air balancing system can eventually be utilized in real duct systems to assess its accuracy and efficiency. The future work to be done includes the improvement of air balancing accuracy, reduction of manual preparatory work and exploring the satisfaction of constraints of absolute pressure level requirements for different rooms, etc. hospital and bio-lab.